Tactile Sensor-Based Steering as a Substitute of the Attendant Joystick in Powered Wheelchairs - Trujillo-León, Andrés; Bachta, Wael; Vidal-Verdú, Fernando (IEEE Transactions on Neural Systems and Rehabilitation Engineering, IEEE, 2018)
Attendant joysticks of powered wheelchairs are devices oriented to help caregivers. Diseases and disabilities such as dementia, spinal cord injuries or blindness make the user unable to drive the chair by his or her own. However, this device is not intuitive to use, especially for old people. Proper processing of the information provided by two tactile sensors in the handlebar achieves control signals that allow an easy and intuitive driving. This is done in this paper, where the performance of this approach is evaluated in comparison with that of the joystick by means of objective measurements as well as questionnaires to obtain the subjective perception of the participants in the experiments. The results show a better performance of the handlebar in terms of error in following a trajectory, collisions with the surrounding furniture, and user feeling related to ease of use, comfort, required training, usefulness, safety, and fatigue.
Keywords: Tecnología de la rehabilitación; Tactile sensors; Wheelchairs; Force; Force sensors; Haptic interfaces; Propulsion; Assistive technology; joystick